Records Committee review for rare bird sighting of Lesser Black-backed Gull at Red Rock Dam, 1996 - Dinsmore, Stephen J.et al (1996)
Records Committee review for a Lesser Black-backed Gull at Red Rock Dam in Marion County, IA on November 27, 1996. Includes a record review document with votes and a documentation form submitted to the committee. Epson - sheet feed